CTLs target Th cells that acquire bystander MHC class I-peptide complex from APCs. - Cox, J; Mcmichael, A; Screaton, G; Xu, X (2007)
CTLs can acquire MHC class I-peptide complexes from their target cells, whereas CD4(+) T cells obtain MHC class II-peptide complexes from APCs in a TCR-specific manner. As a consequence, Ag-specific CTL can kill each other (fratricide) or CD4(+) T cells become APCs themselves. The purpose of the acquisition is not fully understood and may be either inhibition or prolongation of an immunological response. In this study, we demonstrate that human CD4(+) Th cells are able to capture membrane fragments from APC during the process of immunological synapse formation. The fragments contain not only MHC class II-peptide complexes but also MHC class I-peptide complexes, rendering these cells susceptible to CTL killing in an Ag-specific manner. The control of CD4(+) Th cells by Ag-specific CTL, therefore, maybe another mechanism to regulate CD4(+) T cell expansion in normal immune responses or cause immunopathology during the course of viral infections such as HIV.